Altitude Acclimatization Alleviates the Hypoxia-Induced Suppression of Exogenous Glucose Oxidation During Steady-State Aerobic Exercise - Young, Andrew J.; Berryman, Claire E.; Kenefick, Robert W.; Derosier, Allyson N.; Margolis, Lee M.; Wilson, Marques A.; Carrigan, Christopher T.; Murphy, Nancy E.; Carbone, John W.; Rood, Jennifer C.; Pasiakos, Stefan M. (Frontiers in Physiology, 2018)
This study investigated how high-altitude (HA, 4300 m) acclimatization affected exogenous glucose oxidation during aerobic exercise. Sea-level (SL) residents (n = 14 men) performed 80-min, metabolically matched exercise (V˙O2 ∼ 1.7 L/min) at SL and at HA < 5 h after arrival (acute HA, AHA) and following 22-d of HA acclimatization (chronic HA, CHA). During HA acclimatization, participants sustained a controlled negative energy balance (-40%) to simulate the “real world” conditions that lowlanders typically experience during HA sojourns. During exercise, participants consumed carbohydrate (CHO, n = 8, 65.25 g fructose + 79.75 g glucose, 1.8 g carbohydrate/min) or placebo (PLA, n = 6). Total carbohydrate oxidation was determined by indirect calorimetry and exogenous glucose oxidation by tracer technique with 13C. Participants lost (P ≤ 0.05, mean ± SD) 7.9 ± 1.9 kg body mass during the HA acclimatization and energy deficit period. In CHO, total exogenous glucose oxidized during the final 40 min of exercise was lower (P < 0.01) at AHA (7.4 ± 3.7 g) than SL (15.3 ± 2.2 g) and CHA (12.4 ± 2.3 g), but there were no differences between SL and CHA. Blood glucose and insulin increased (P ≤ 0.05) during the first 20 min of exercise in CHO, but not PLA. In CHO, glucose declined to pre-exercise concentrations as exercise continued at SL, but remained elevated (P ≤ 0.05) throughout exercise at AHA and CHA. Insulin increased during exercise in CHO, but the increase was greater (P ≤ 0.05) at AHA than at SL and CHA, which did not differ. Thus, while acute hypoxia suppressed exogenous glucose oxidation during steady-state aerobic exercise, that hypoxic suppression is alleviated following altitude acclimatization and concomitant negative energy balance.